Gambaran Dukungan Sosial Ibu Hamil dengan Preeklampsia di RSUD Dr. Abdoer Rahem Situbondo - Dwi Siska Hardiyanti; Dini Kurniawati; Peni Juliningrum Perdani (Pustaka Kesehatan, 2021)
The first cause of maternal death in East Java is caused by preeclampsia. The impact of preeclampsia can be physiological and psychological. The other impact is driven by the lack of social support like husbands’ support, families, friends, and the environment, which could worsen mothers’ preeclampsia. Social support can encourage pregnant women with preeclampsia to overcome stress, anxiety, and depression. The study was to describe the social support of pregnant women with preeclampsia at dr. Abdoer Rahem hospital Situbondo. This study used a descriptive-analytic study with a total sample of 60 pregnant women with preeclampsia. The instrument in this study used a Medical Outcomes Study: Social Support Survey (MOS-SSS) questionnaire consisting of 19 questions. Data analysis in this study used univariate analysis. The results of this study indicate that the value of social support in 60 respondents is in a moderate condition (51.7%). This case requires good social support to motivate mothers to improve their health status. In increasing social support, the relations of pregnant women with preeclampsia are included in giving health care workers information and education.